An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids - Arachchige, Gayashan M.; Jayakody, Sevvandi; Mooi, Rich; Kroh, Andreas (Zootaxa, 2019)
The first recorded regular echinoid species from Sri Lanka, “Salmacis virgulatus” (now known as S. virgulata L. Agassiz in L. Agassiz & Desor, 1846), was listed by Agassiz & Desor (1846). Knowledge of Sri Lankan regular echinoids continued to advance until the end of the 19th century. However, there is a gap in knowledge between the mid-20th and the beginning of the 21st centuries due to a lack of systematic studies, with the exception of two checklists published by the IUCN Red List in 2006 and 2012. In the present study, we compiled a species list combining published data and new data based on fieldwork between 2013 and 2015. Echinoids were sampled by snorkelling, diving, examination of fisheries bycatch, and collection of tests from beaches. The updated species list presented in this study includes 39 regular echinoids belonging to 28 genera, nine families, and five orders. Phyllacanthus imperialis (Lamarck, 1816) and Temnopleurus toreumaticus (Leske, 1778), which were not recorded during the last 90 years, were confirmed to still occur in Sri Lanka by the present study. We develop an updated species list of regular echinoids to form a basis for future systematic work. The study recommends further investigation to evaluate the status of deep-sea species and additional field work off the northern and eastern coasts of Sri Lanka.